(x+y)dy/dx = x^2+xy+x+1 ; y=v-x So i did the substitution and ended up with vdv/dx - v =xv+x+1 and, if correct, i've no idea how to solve.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Erghhh (x+y)dy/dx = x^2+xy+x+1 ; y=v-x So i did the substitution and ended up with vdv/dx - v =xv+x+1 and, if correct, i've no idea how to solve. (x+y)dy/dx = x^2+xy+x+1 ; y=v-x vdv/dx - v =xv+x+1 vdv/dx = v+xv+x+1 vdv/dx = v(1+x) + (1+x) vdv/dx = (v+1)(1+x) Integrate both sides Integrate this thing and enjoy the sunny day
So then i got (y+x)ln|x+y+1|=(1/2)(x^2) +x+c The answer, according to my book, is y=ln|x+y+1| +(1/2)(x^2)+C I'm unsure of how to get there..
Hi A sign - is missing (y+x)-ln|x+y+1|=(1/2)(x^2) +x+c Then y=ln|x+y+1| +(1/2)(x^2)+c
Can you explain where that minus sign has come from?
Intgrate that. running-gag got in ahead of me!
View Tag Cloud